Remnants of Cardinal Symptoms of Parkinson's Disease, Not Dyskinesia, Are Problematic for Dyskinetic Patients Performing Activities of Daily Living - Goubault, Etienne; Nguyen, Hung P.; Bogard, Sarah; Blanchet, Pierre J.; Bézard, Erwan; Vincent, Claude; Sarna, Justyna; Monchi, Oury; Duval, Christian (Frontiers in Neurology, 2019)
Introduction. The impact of drug-induced dyskinesia (DID) on the daily lives of patients with Parkinson’s disease (PD) remains to be determined. Furthermore, evidence suggests that cardinal motor symptoms of PD may coexist with DID, but their impact on activities of daily living (ADL) relative to DID is not known. This cross-sectional study aimed at determining the effect of DID and cardinal motor symptoms of PD on ADL in patients who were experiencing peak-dose choreic-type DID. Method. 121 patients diagnosed with PD known to experience choreic-type DID were recruited for the study. Patients were asked to perform a set of ADL. Levels of DID, tremor, bradykinesia, and freezing of gait were measured using 17 inertial sensors design to capture full body movement, while rigidity and postural instability were assessed using clinical evaluations. Cognition was also assessed using the mini-mental state examination. Success criteria were set for each ADL using the time needed to perform the task and errors measured in 69 age-gender-matched healthy controls. Binary logistic regressions were used to identify symptoms influencing success or failure for each activity. Receiver operating characteristic curves were computed on each significant symptom, and Youden indexes were calculated to determine the critical level of symptomatology at which the performance significantly changed. Results. Results show that 97.7% of patients who presented with DID during the experiment also presented with at least one cardinal motor symptom. On average, patients took more time and did more errors during ADL. Multivariate analyses revealed that for the great majority of ADL, DID were not associated with worsening of performance; however, postural instability, tremor, rigidity, and cognitive decline significantly decreased the odds of success. Conclusions. Residual symptoms of PD, defined as cardinal symptoms of PD still present at peak-dose, but also cognitive decline, are more problematic than DID in the performance of ADL for patients experiencing slight-to-moderate DID. Therefore, a strategy using lower doses of medication to manage DID may be counterproductive since it would not address these symptoms already present in patients.